Preparation method of square lithium ion battery for energy storage
By using the mixing and specific coating welding technology of lithium iron phosphate active material and graphene composite conductive paste in lithium-ion batteries, square lithium-ion batteries with long life and high power are prepared, solving the uncertainty of lithium-ion battery life The problem of poor compatibility with high power improves the service life and adaptability of the energy storage system.
Patent Information
- Application Number
- CN202411419282.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The life of existing lithium-ion batteries is uncertain and have poor high power compatibility, which cannot meet the needs of large-scale energy storage scenarios.
Using a square lithium-ion battery preparation method for energy storage, a long cycle life and High power charging and discharging battery.
It realizes diversified energy storage applications of lithium-ion batteries, extends the service life of the energy storage system, and can effectively deal with a variety of large-scale energy storage scenarios.
Smart Images

Figure CN119315125A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a square lithium ion battery for energy storage. Background Art
[0002] New energy storage represented by lithium-ion batteries has a short construction cycle, strong regulation capabilities, and broad development space, representing the direction of future development; power battery energy storage has bidirectional millisecond-level rapid regulation capabilities, and can play a huge role in power system flexibility regulation, emergency power support, and accident backup. It is an effective means to address the problems of power balance and safety and stability.
[0003] With the application of electrochemical energy storage, the cost will be further reduced, and its advantages such as flexible layout, fast response speed and high energy efficiency will continue to stand out.
[0004] However, there is still a certain degree of uncertainty in the battery life of new energy storage technologies. If the battery life is too short, the service life of the energy storage system will be greatly reduced. Lithium-ion battery energy storage products have a single function. Even if they have a long cycle life, they often cannot have high power and cannot cope with large-scale energy storage scenarios. In summary, it is crucial to provide a long-life and high-power energy storage battery. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a square lithium-ion battery for energy storage, so as to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a square lithium-ion battery for energy storage, comprising the following steps:
[0007] Step 1, mixing the lithium iron phosphate active material, the graphene composite conductive slurry and polyvinylidene fluoride according to a mass ratio, then adding N-methylpyrrolidone, stirring under a vacuum stirrer, to obtain a positive electrode slurry;
[0008] Step 2, the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried in a coating oven, and then cold pressed, cut and sliced to obtain a positive electrode sheet;
[0009] Step 3, the active material with graphite, the conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a certain mass ratio, and then deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry;
[0010] Step 4, uniformly coating the negative electrode slurry on the negative electrode current collector copper foil, drying in a coating oven, and then cold pressing, slitting, and sheeting to obtain a negative electrode sheet;
[0011] Step 5, providing a lithium-ion battery separator;
[0012] Step 6: stack the positive electrode sheet, the separator, and the negative electrode sheet in order to obtain a bare cell;
[0013] Step 7, providing a square lithium-ion battery aluminum shell, a positive electrode cover plate, a negative electrode cover plate, a positive electrode isolation ring, a Mylar film, and a side support sheet;
[0014] Step 8, the bare cell is first welded to the negative electrode cover plate, and after being wrapped and fixed with a Mylar film, a side support sheet, and a positive electrode isolation ring, it is placed in a square lithium-ion battery aluminum shell, and then the tabs of the positive electrode sheet are welded to the positive electrode cover plate respectively;
[0015] Step 9, sealing and welding the negative electrode cover plate, the positive electrode cover plate and the square lithium-ion battery aluminum shell to obtain a semi-finished battery cell before liquid injection;
[0016] Step 10: The semi-finished battery cell before liquid injection is subjected to baking, liquid injection, formation, secondary liquid injection, sealing, and capacity division to obtain a square lithium-ion battery for energy storage.
[0017] Wherein, in step 1, the particles with lithium iron phosphate active material have an average particle size of 30 to 200 nm and a specific surface area of 5 to 30 m 2 / g;
[0018] The mass ratio of the lithium iron phosphate active material, the graphene composite conductive paste, polyvinylidene fluoride and N-methylpyrrolidone is: 100: 0.8-1: 2-2.5: 30-60;
[0019] The vacuum degree of the stirrer is -60 to -80 kPa.
[0020] Wherein, in step 2, the density of the positive electrode slurry coated on the positive electrode current collector aluminum foil is 200-400 mg / m 2 , coating speed is 1~10m / min;
[0021] The oven temperature is 65-100°C;
[0022] The cold pressing roller pressure is 20-40T, the sheet length is 200mm-300mm, the sheet width is 80-150mm, the positive electrode sheet length is 10-40mm, and the positive electrode sheet width is 20-50mm.
[0023] Wherein, in step 3, the conductive agent is one or a mixture of conductive carbon black, carbon nanotubes and conductive graphite, the active material with graphite is one of primary particle artificial graphite and secondary particle artificial graphite, and the active material with graphite has a D50 particle size of 8 to 15 μm and a specific surface area of 1 to 10 m 2 / g.
[0024] Wherein, in step 3, the mass ratio of the active material with graphite, the conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber is 90-96: 0.5-1: 1.5-2.5: 1-3;
[0025] The vacuum degree of the stirrer is -60 to -80 kPa.
[0026] Wherein, in step 4, the density of the negative electrode slurry coated on the negative electrode current collector copper foil is 100-200 mg / m 2 , coating speed is 1~10m / min;
[0027] The oven temperature is 65-100°C;
[0028] The cold pressing roller pressure is 20-40T, the sheet length is 200mm-300mm, the sheet width is 80-150mm, the negative electrode sheet length is 10-40mm, and the negative electrode sheet width is 20-50mm.
[0029] Wherein, in step 5, the thickness of the diaphragm is 7 to 25 μm and the width is 210 to 310 mm;
[0030] In step 6, the numerical relationship between the thickness H of the laminate of the bare cell and the thickness H3 of the aluminum shell of the square lithium-ion battery satisfies 90%≤H / H3≤97%.
[0031] Among them, in step 7, the square lithium-ion battery aluminum shell has a special length-width ratio, length L1, width W1, large wall thickness H1, side wall thickness H2, the numerical relationship between W1 and L1 satisfies 90mm≤W1≤130mm and 2.7≤L1 / W1≤2.9, the numerical relationship between H1 and H2 satisfies H1 / H2=2 / 3, the square lithium-ion battery aluminum shell is a hollow shape, and the positive cover plate and the negative cover plate act on the two ends of the square lithium-ion battery aluminum shell respectively.
[0032] Wherein, in step 8, the welding method of the positive electrode tab and the positive electrode cover is one of laser, ultrasonic and friction welding; the Mylar film is fixed to the negative electrode cover and the positive electrode isolation ring by hot melting points, and the number of hot melting points is 3 to 6 on the large surface and 1 to 3 on the side;
[0033] In step 9, the negative electrode cover plate, the positive electrode cover plate and the aluminum shell of the lithium-ion battery are welded by one of ultrasonic, friction and laser welding.
[0034] Wherein, in step 10, ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an organic solvent; lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are dissolved in the organic solvent to prepare an electrolyte with a concentration of 1.05 mol / L;
[0035] The electrolyte contains 10% to 15% lithium hexafluorophosphate and 1% to 5% lithium bis(fluorosulfonyl)imide.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention uses a method for preparing a square lithium-ion battery for energy storage to prepare a diversified lithium-ion battery for energy storage, which has both a long cycle life and high-power charging and discharging capabilities, which will greatly increase the service life of the energy storage system and can easily cope with a variety of large-scale energy storage scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a three-dimensional diagram of the aluminum shell of a square lithium-ion battery of the present invention;
[0039] Figure 2 This is a schematic diagram of the explosion structure of a square lithium-ion battery of the present invention;
[0040] Figure 3 The conventional performance of the battery of the present invention changes with the number of cycles;
[0041] Figure 4 The figure is a curve diagram showing the change of high power performance of the battery of the present invention with the number of cycles.
[0042] In the figure, 1. square lithium-ion battery aluminum shell; 2. bare battery cell; 3. Mylar film; 4. side support plate; 5. negative electrode cover plate; 6. positive electrode cover plate; 7. positive electrode isolation ring. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Embodiment 1:
[0045] A method for preparing a square lithium-ion battery for energy storage comprises the following steps:
[0046] Step 1: Mix the lithium iron phosphate active material, graphene composite conductive slurry and polyvinylidene fluoride in a mass ratio of 96:2:2, then add N-methylpyrrolidone, and stir under a vacuum stirrer at a vacuum degree of -60 kPa to -80 kPa to obtain a positive electrode slurry.
[0047] Step 2: Evenly coat the positive electrode slurry on the positive electrode current collector aluminum foil with a coating density of 200 to 400 mg / m 2, the coating speed is 1-10m / min, and the coating oven is dried at a temperature of 65-100°C. Then, the cold roller press pressure is 20-40T, slitting, and sheeting, the sheeting length is 200mm-300mm, the sheeting width is 80-150mm, the positive electrode sheet length is 10-40mm, and the positive electrode sheet width is 20-50mm to obtain the positive electrode sheet.
[0048] Step 3: Mix the active material with graphite, the conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96:0.5:1.5:2, then add deionized water, and stir under a vacuum mixer at a vacuum degree of -60 kPa to -80 kPa to obtain a negative electrode slurry.
[0049] Step 4: evenly coat the negative electrode slurry on the negative electrode current collector copper foil, with a single-sided coating density of 100 to 200 mg / m 2 The coating speed is 1 to 10 m / min, and the coating is dried in a coating oven at a temperature of 65 to 100°C, and then cold pressed at a roller pressure of 20 to 40T, cut and sliced, the slice length is 200 mm to 300 mm, the slice width is 80 to 150 mm, the negative electrode sheet length is 10 to 40 mm, and the negative electrode sheet width is 20 to 50 mm to obtain a negative electrode sheet.
[0050] Step 5, providing a lithium-ion battery separator, the separator having a thickness of 7 to 25 μm and a width of 210 to 310 mm;
[0051] Step 6: stack the positive electrode sheet, the separator, and the negative electrode sheet in order to obtain a bare battery cell 2; the numerical relationship between the stacking thickness H of the bare battery cell 2 and the aluminum shell thickness H3 satisfies 90%≤H / H3≤97%.
[0052] Step 7, provide a square lithium-ion battery aluminum shell 1, a positive electrode cover plate 6, a negative electrode cover plate 5, a positive electrode isolation ring 7, a Mylar film 3, and a side support plate 4; the square lithium-ion battery aluminum shell 1 has a special length-width ratio. Length L1, width W1, large surface wall thickness H1, side wall thickness H2, W1, L1 numerical relationship satisfies 90mm≤W1≤130mm and 2.7≤L1 / W1≤2.9, H1, H2 numerical relationship satisfies H1 / H2=2 / 3. The square lithium-ion battery aluminum shell 1 is a hollow shape, and the positive electrode cover plate 6 and the negative electrode cover plate 5 act on the two ends of the square lithium-ion battery aluminum shell 1.
[0053] Step 8, the bare battery cell 2 is first welded to the negative electrode cover plate 5, and after being wrapped and fixed by the Mylar film 3, the side support sheet 4, and the positive electrode isolation ring 7, it is placed in the square lithium-ion battery aluminum shell 1, and then the pole ears of the positive electrode plate are welded to the positive electrode cover plate 6 respectively; the welding method of the pole ears of the positive electrode plate and the positive electrode cover plate 6 is one of laser, ultrasonic and friction welding; the Mylar film 3 and the negative electrode cover plate 5 and the positive electrode isolation ring 7 are fixed by hot melting points, and the number of hot melting points is 3 to 6 on the large surface and 1 to 3 on the side.
[0054] Step 9, seal and weld the negative electrode cover plate 5, the positive electrode cover plate 6 and the square lithium-ion battery aluminum shell 1 to obtain a semi-finished battery cell before liquid injection; the welding method of the negative electrode cover plate 5, the positive electrode cover plate 6 and the square lithium-ion battery aluminum shell 1 is one of ultrasonic, friction and laser welding.
[0055] Step 10: The semi-finished battery cell before liquid injection is baked, liquid injected (the volume ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in the electrolyte is 1:1:1, the content of lithium hexafluorophosphate is 12.5%, and the content of lithium bis(fluorosulfonyl)imide is 3%), chemically formed, liquid injected a second time, sealed, and volume divided to obtain a square lithium-ion battery for energy storage.
[0056] Embodiment 2:
[0057] A method for preparing a square lithium-ion battery for energy storage comprises the following steps:
[0058] Step 1: Mix the lithium iron phosphate active material, graphene composite conductive slurry and polyvinylidene fluoride in a mass ratio of 96.5:1.5:2, then add N-methylpyrrolidone, and stir under a vacuum stirrer at a vacuum degree of -60 kPa to -80 kPa to obtain a positive electrode slurry.
[0059] Step 2: Evenly coat the positive electrode slurry on the positive electrode current collector aluminum foil with a coating density of 200 to 400 mg / m 2 , the coating speed is 1-10m / min, and the coating oven is dried at a temperature of 65-100°C. Then, the cold roller press pressure is 20-40T, slitting, and sheeting, the sheeting length is 200mm-300mm, the sheeting width is 80-150mm, the positive electrode sheet length is 10-40mm, and the positive electrode sheet width is 20-50mm to obtain the positive electrode sheet.
[0060] Step 3: Mix the active material with graphite, the conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96:0.5:1.5:2, then add deionized water, and stir under a vacuum mixer at a vacuum degree of -60 kPa to -80 kPa to obtain a negative electrode slurry.
[0061] Step 4: evenly coat the negative electrode slurry on the negative electrode current collector copper foil, with a single-sided coating density of 100 to 200 mg / m 2 The coating speed is 1 to 10 m / min, and the coating is dried in a coating oven at a temperature of 65 to 100°C, and then cold pressed at a roller pressure of 20 to 40T, cut and sliced, the slice length is 200 mm to 300 mm, the slice width is 80 to 150 mm, the negative electrode sheet length is 10 to 40 mm, and the negative electrode sheet width is 20 to 50 mm to obtain a negative electrode sheet.
[0062] Step 5, providing a lithium-ion battery separator, the separator having a thickness of 7 to 25 μm and a width of 210 to 310 mm;
[0063] Step 6: stack the positive electrode sheet, the separator, and the negative electrode sheet in order to obtain a bare battery cell 2; the numerical relationship between the stacking thickness H of the bare battery cell 2 and the aluminum shell thickness H3 satisfies 90%≤H / H3≤97%.
[0064] Step 7, provide a square lithium-ion battery aluminum shell 1, a positive electrode cover plate 6, a negative electrode cover plate 5, a positive electrode isolation ring 7, a Mylar film 3, and a side support plate 4; the square lithium-ion battery aluminum shell 1 has a special length-width ratio. Length L1, width W1, large surface wall thickness H1, side wall thickness H2, W1, L1 numerical relationship satisfies 90mm≤W1≤130mm and 2.7≤L1 / W1≤2.9, H1, H2 numerical relationship satisfies H1 / H2=2 / 3. The square lithium-ion battery aluminum shell 1 is a hollow shape, and the positive electrode cover plate 6 and the negative electrode cover plate 5 act on the two ends of the square lithium-ion battery aluminum shell respectively.
[0065] Step 8, the bare battery cell 2 is first welded to the negative electrode cover plate 5, and after being wrapped and fixed by the Mylar film 3, the side support sheet 4, and the positive electrode isolation ring 7, it is placed in the square lithium-ion battery aluminum shell 1, and then the pole ears of the positive electrode plate are welded to the positive electrode cover plate 6 respectively; the welding method of the pole ears of the positive electrode plate and the positive electrode cover plate 6 is one of laser, ultrasonic and friction welding; the Mylar film 3 and the negative electrode cover plate 5 and the positive electrode isolation ring 7 are fixed by hot melting points, and the number of hot melting points is 3 to 6 on the large surface and 1 to 3 on the side.
[0066] Step 9, seal and weld the negative electrode cover plate 5, the positive electrode cover plate 6 and the square lithium-ion battery aluminum shell 1 to obtain a semi-finished battery cell before liquid injection; the welding method of the negative electrode cover plate 5, the positive electrode cover plate 6 and the square lithium-ion battery aluminum shell 1 is one of ultrasonic, friction and laser welding.
[0067] Step 10: The semi-finished battery cell before liquid injection is baked, liquid injected (the volume ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in the electrolyte is 1:1:1, the content of lithium hexafluorophosphate is 11.5%, and the content of lithium bis(fluorosulfonyl)imide is 3.5%), chemically formed, liquid injected a second time, sealed, and volume divided to obtain a square lithium-ion battery for energy storage.
[0068] Embodiment 3:
[0069] A method for preparing a square lithium-ion battery for energy storage comprises the following steps:
[0070] Step 1: Mix the lithium iron phosphate active material, graphene composite conductive slurry and polyvinylidene fluoride in a mass ratio of 95.5:2.5:2, then add N-methylpyrrolidone, and stir under a vacuum stirrer at a vacuum degree of -60 kPa to -80 kPa to obtain a positive electrode slurry.
[0071] Step 2: Evenly coat the positive electrode slurry on the positive electrode current collector aluminum foil with a coating density of 200 to 400 mg / m 2 , the coating speed is 1-10m / min, and the coating oven is dried at a temperature of 65-100°C. Then, the cold roller press pressure is 20-40T, slitting, and sheeting, the sheeting length is 200mm-300mm, the sheeting width is 80-150mm, the positive electrode sheet length is 10-40mm, and the positive electrode sheet width is 20-50mm to obtain the positive electrode sheet.
[0072] Step 3: Mix the active material with graphite, the conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96:0.5:1.5:2, then add deionized water, and stir under a vacuum mixer at a vacuum degree of -60 kPa to -80 kPa to obtain a negative electrode slurry.
[0073] Step 4: evenly coat the negative electrode slurry on the negative electrode current collector copper foil, with a single-sided coating density of 100-200 mg / m2 and a coating speed of 1-10 m / min. Dry the coating in an oven at a temperature of 65-100°C, then cold press, with a roller pressure of 20-40T, cut and slice, with a slice length of 200-300 mm and a slice width of 80-150 mm. The length of the negative electrode sheet is 10-40 mm, and the width of the negative electrode sheet is 20-50 mm to obtain a negative electrode sheet.
[0074] Step 5, providing a lithium-ion battery separator, the separator having a thickness of 7 to 25 μm and a width of 210 to 310 mm;
[0075] Step 6: stack the positive electrode sheet, the separator, and the negative electrode sheet in order to obtain a bare battery cell 2; the numerical relationship between the stacking thickness H of the bare battery cell 2 and the aluminum shell thickness H3 satisfies 90%≤H / H3≤97%.
[0076] Step 7, provide a square lithium-ion battery aluminum shell 1, a positive electrode cover plate 6, a negative electrode cover plate 5, a positive electrode isolation ring 7, a Mylar film 3, and a side support plate 4; the square lithium-ion battery aluminum shell 1 has a special length-width ratio. Length L1, width W1, large surface wall thickness H1, side wall thickness H2, W1, L1 numerical relationship satisfies 90mm≤W1≤130mm and 2.7≤L1 / W1≤2.9, H1, H2 numerical relationship satisfies H1 / H2=2 / 3. The square lithium-ion battery aluminum shell 1 is a hollow shape, and the positive electrode cover plate 6 and the negative electrode cover plate 5 act on the two ends of the square lithium-ion battery aluminum shell 1 respectively.
[0077] Step 8, the bare battery cell 2 is first welded to the negative electrode cover plate 5, and after being wrapped and fixed by the Mylar film 3, the side support sheet 4, and the positive electrode isolation ring 7, it is placed in the square lithium-ion battery aluminum shell 1, and then the pole ears of the positive electrode plate are welded to the positive electrode cover plate 6 respectively; the welding method of the pole ears of the positive electrode plate and the positive electrode cover plate 6 is one of laser, ultrasonic and friction welding; the Mylar film 3 and the negative electrode cover plate 5 and the positive electrode isolation ring 7 are fixed by hot melting points, and the number of hot melting points is 3 to 6 on the large surface and 1 to 3 on the side.
[0078] Step 9, seal and weld the negative electrode cover plate 5, the positive electrode cover plate 6 and the square lithium-ion battery aluminum shell 1 to obtain a semi-finished battery cell before liquid injection; the welding method of the negative electrode cover plate 5, the positive electrode cover plate 6 and the square lithium-ion battery aluminum shell 1 is one of ultrasonic, friction and laser welding.
[0079] Step 10: The semi-finished battery cell before liquid injection is baked, liquid injected (the volume ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in the electrolyte is 1:1:1, the content of lithium hexafluorophosphate is 11.5%, and the content of lithium bis(fluorosulfonyl)imide is 4%), chemically formed, liquid injected a second time, sealed, and volume divided to obtain a square lithium-ion battery for energy storage.
[0080] Example
[0081] Battery samples were taken from Examples 1-3 for testing, and the test types, results and testing methods are shown in the following table:
[0082] Table 1 Battery property test data
[0083]
[0084] The specific battery cycle number is as follows Figure 3 , as shown in 4.
[0085] From Table 1 and Figure 3,4 It can be seen that through the preparation method of square lithium-ion batteries for energy storage, diversified lithium-ion batteries for energy storage are prepared. The mass energy density of the diversified lithium-ion batteries for energy storage can reach 182Wh / kg. At the same time, it has a long life at room temperature 1C / 1C (100A / 100A) of about 4000 cycles and a high power 2C / 3C (200A / 300A) of about 2000 cycles. It has both a long cycle life and high power charging and discharging capabilities, which will greatly improve the service life of the energy storage system and can easily cope with a variety of large-scale energy storage scenarios.
[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a square lithium-ion battery for energy storage, characterized in that: The following steps are involved: Step 1, mixing the lithium iron phosphate active material, the graphene composite conductive slurry and polyvinylidene fluoride according to a mass ratio, then adding N-methylpyrrolidone, stirring under a vacuum stirrer, to obtain a positive electrode slurry; Step 2, the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, dried in a coating oven, and then cold pressed, cut and sliced to obtain a positive electrode sheet; Step 3, the active material with graphite, the conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a certain mass ratio, and then deionized water is added, and the mixture is stirred under a vacuum mixer to obtain a negative electrode slurry; Step 4, uniformly coating the negative electrode slurry on the negative electrode current collector copper foil, drying in a coating oven, and then cold pressing, slitting, and sheeting to obtain a negative electrode sheet; Step 5, providing a lithium-ion battery separator; Step 6: stack the positive electrode sheet, the separator, and the negative electrode sheet in order to obtain a bare cell; Step 7, providing a square lithium-ion battery aluminum shell, a positive electrode cover plate, a negative electrode cover plate, a positive electrode isolation ring, a Mylar film, and a side support sheet; Step 8, the bare cell is first welded to the negative electrode cover plate, and after being wrapped and fixed with a Mylar film, a side support sheet, and a positive electrode isolation ring, it is placed in a square lithium-ion battery aluminum shell, and then the tabs of the positive electrode sheet are welded to the positive electrode cover plate respectively; Step 9, sealing and welding the negative electrode cover plate, the positive electrode cover plate and the square lithium-ion battery aluminum shell to obtain a semi-finished battery cell before liquid injection; Step 10: The semi-finished battery cell before liquid injection is subjected to baking, liquid injection, formation, secondary liquid injection, sealing, and capacity division to obtain a square lithium-ion battery for energy storage.
2. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 1, the particles with lithium iron phosphate active material have an average particle size of 30 to 200 nm and a specific surface area of 5 to 30 m 2 / g; The mass ratio of the lithium iron phosphate active material, the graphene composite conductive paste, polyvinylidene fluoride and N-methyl pyrrolidone is: 100: 0.8-1: 2-2.5: 30-60; The vacuum degree of the stirrer is -60 to -80 kPa.
3. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 2, the density of the positive electrode slurry coated on the positive electrode current collector aluminum foil is 200-400 mg / m 2 , coating speed is 1~10m / min; The oven temperature is 65-100°C; The cold pressing roller pressure is 20-40T, the sheet length is 200mm-300mm, the sheet width is 80-150mm, the positive electrode sheet length is 10-40mm, and the positive electrode sheet width is 20-50mm.
4. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 3, the conductive agent is one or a mixture of conductive carbon black, carbon nanotubes and conductive graphite, the active material with graphite is one of primary particle artificial graphite and secondary particle artificial graphite, and the active material with graphite has a D50 particle size of 8 to 15 μm and a specific surface area of 1 to 10 m 2 / g.
5. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 3, the mass ratio of the active material with graphite, the conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber is 90-96: 0.5~1:1.5~2.5:1~3; The vacuum degree of the stirrer is -60 to -80 kPa.
6. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 4, the density of the negative electrode slurry coated on the negative electrode current collector copper foil is 100-200 mg / m 2 , coating speed is 1~10m / min; The oven temperature is 65-100°C; The cold pressing roller pressure is 20-40T, the sheet length is 200mm-300mm, the sheet width is 80-150mm, the negative electrode sheet length is 10-40mm, and the negative electrode sheet width is 20-50mm.
7. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 5, the thickness of the diaphragm is 7 to 25 μm and the width is 210 to 310 mm; In step 6, the numerical relationship between the thickness H of the laminate of the bare cell and the thickness H3 of the aluminum shell of the square lithium-ion battery satisfies 90%≤H / H3≤97%.
8. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 7, the square lithium-ion battery aluminum shell has a special length-width ratio, length L1, width W1, large wall thickness H1, side wall thickness H2, the numerical relationship between W1 and L1 satisfies 90mm≤W1≤130mm and 2.7≤L1 / W1≤2.9, the numerical relationship between H1 and H2 satisfies H1 / H2=2 / 3, the square lithium-ion battery aluminum shell is a hollow shape, and the positive cover plate and the negative cover plate act on the two ends of the square lithium-ion battery aluminum shell respectively.
9. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 8, the positive electrode tab and the positive electrode cover are welded by one of laser, ultrasonic and friction welding; the Mylar film is fixed to the negative electrode cover and the positive electrode isolation ring by hot melting points, with 3 to 6 hot melting points on the large surface and 1 to 3 on the side; In step 9, the negative electrode cover plate, the positive electrode cover plate and the aluminum shell of the lithium-ion battery are welded by one of ultrasonic, friction and laser welding.
10. The method for preparing a square lithium-ion battery for energy storage according to claim 1, characterized in that: In step 10, ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an organic solvent; lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are dissolved in the organic solvent to prepare an electrolyte with a concentration of 1.05 mol / L; The electrolyte contains 10% to 15% lithium hexafluorophosphate and 1% to 5% lithium bis(fluorosulfonyl)imide.
Citation Information
Patent Citations
High-energy-density square laminated lithium ion battery and preparation method thereof
CN111477771A
Lithium ion battery with square metal shell and assembly process of lithium ion battery
CN114335919A
Assembly method of laminated lithium battery and laminated lithium battery
CN115149069A
Preparation method of lithium ion battery
CN116544393A
Lithium ion battery
CN201345385Y